KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH UMUM TINGKAT SMA/ SMK KABUPATEN MAGELANG - Jaka Siswanta (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2012)
The problems on this research are: (1) How is the Islamic Religious Teacher characteristic of SMA/SMK in Magelang? (2) How is the professional competence of Islamic Religious Teacher of SMA/SMK in Magelang? (3) What factors influence the Islamic Religious Teacher professional competence of SMA/SMK in Magelang? This research was applying qualitative method by developing etno-methodology model. The subject of the research was Islamic Religious Teacher in 11 different SMA/SMK. Observation and interview was applied to collect the data. The finding of the research showed that: 1) from 11 teachers, ten are graduated from Islamic teacher education and one from Syariah. They have more than ten year experiences in teaching. 2) They all have religious, social, and professional religious background. 3) The dominant factor influences their professional competence is on teaching experiences and motivation on doing their job.